Augmented Reality (AR) Sandbox: 3-Dimensional Media to Learn Topographic Maps - Septi Nur Afifah, Dian; Ilman Nafi’an, Muhammad; Linggo Wati, Tri; Ariyanti, Novia; ., Sutopo; ., . (International Journal of Engineering and Technology, 2018)
This research focuses on the literature on the introduction of learning media or apparatus that can introduce topographic maps through augmented reality sandbox in 3-dimensional form. The study presents a specific AR system called Augmented Reality (AR) Sandbox. Data analysis through source triangulation techniques. By validating media feasibility, the AR sandbox is classified as a good learning device when used in learning topographic maps or learning to recognize the shape of the earth's face. However, based on the review literature in these two literature, it has not provided much or less complete references because of the limitations of device development. By using this media, students can distinguish how the shape of the highlands and lowlands, or know the conditions in the ocean to the sea trench.Â
Keywords: Augmented Reality Sandbox; Topographic Maps; AR; 3 Dimensional